A new Channel and QoS Aware Scheduler algorithm for real time and non real time traffic in 5G heterogeneous networks - Andrade Queiroz, Gabriel; Rosa da Silva, Ederson (Revista IEEE América Latina, 2024)
5G mobile communication systems have increasing demands related to Quality of Service (QoS) parameters integrated with high user densification in heterogeneous network scenarios. In this sense, 5G networks are expected to handle a wide range of applications and services. Therefore, scheduling algorithms that can benefit users of real-time (RT) and non-real-time (NRT) applications are studied. System-level simulations are carried out to analyze the performance of a new proposed Channel and Quality of Service Aware scheduler (CQAS) and compare it to Round Robin (RR), Best Channel Quality Indicator (CQI), and QoS Aware Scheduler (QAS) in a heterogeneous network with multiple traffic models while varying the number of users to stress test the network. The results show that CQAS has significant gains in overall throughput and latency while performing well in the reliability and fairness index.